Mode of Actions and Pathogenicity of 11 Endophytic Fungi on Fusarium oxysporum - Restu Aminningsih; Tunjung Pamekas; Hendri Bustamam (AGRITROPICA : Journal of Agricultural Sciences, 2021)
Fusarium oxysporum is the pathogenic cause of the disease on chili plants that can reduce production in the cultivation process that needs to be done to control an environmentally friendly manner using endophytic fungi. This study aims to test the inhibition, the mechanism of antagonism, and pathogenicity of eleven endophytic fungi origin of pepper plants Bengkulu province against the pathogen Fusarium oxysporum in vitro. Research conducted in the Laboratory of Plant Protection, Faculty of Agriculture, University of Bengkulu from December 2020 to February 2021. The study consists of: the rejuvenation of the fungi isolates of endophytic and fungi pathogens Fusarium oxysporum, dual culture test, the mechanism of antagonism test, as well as pathogenesis endophytic fungi test. Endophytic fungi isolate obtained from the collection of the laboratory of Plant Protection, University of Bengkulu. The results of the research show from eleven endophytic fungi only 1 endophytic fungi which has a percentage of inhibition of 50% of the isolates of Rhizoctonia sp.2. The mechanism of antagonism occurs consisting of the competition between the space of nutrients and oxygen, hiperparasitisme, and antibiosis. patogenensitas test show only isolates of Rhizoctonia sp.2 that do not produce patches on the chili seeds.